Riview Artikel : Retinol Pada Kosmetik - Putri Wulan Birru; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Retinoids are a cosmetic ingredient with side effects such as anti-aging or reducing acne. The use of retinol in cosmetics is provided in creams, gels, and serums. Using 0.1% retinol for two weeks will show the desired results. The use of cosmetics has effects such as: whitening the skin, preventing wrinkles and fine lines on the skin, and being able to protect the skin from sun exposure, treating dry skin, and treating acne-prone skin in anti-aging using a method from a journal, namely the Wilcoxon test. The results for use in adolescents and mothers are around 1.4 after using it; it has increased by around 1.8, and the results of the Wilcoxon testing method it says that the use of anti-aging cosmetics will experience changes in skin texture, such as wrinkles, the face becomes smoother, the facial skin becomes tighter